A mathematical model for understanding and controlling monkeypox transmission dynamics in the USA and its implications for future epidemic management - Md. Azmir Ibne Islam; M.H.M. Mubassir; Arindam Kumar Paul; Sharmin Sultana Shanta (Decoding Infection and Transmission)
Background: Although outbreaks of human monkeypox (mpox) caused by the monkeypox virus (MPXV) have decreased globally, little is known about the short-term dynamics of this disease, thus highlighting a critical need to assess the underlying interventions. Methods: To identify and re-examine the key patterns of the disease, in this paper, a modified logistic growth model is presented and analysed. Our main focus is on the two non-pharmaceutical interventions: policies aimed at reducing human-to-human transmission and animal-to-human transmission. We incorporated these two strategies in the model as control parameters to understand their short-term significance on epidemics, and to analyse their strengths in minimizing the infected cases. The mpox data set of the USA from 10 May 2022 to 31 December 2022 was used in the model and the baseline parameters were estimated. Results: The model reveals a complying acceptance to the USA data set. Model simulations highlight that preventive measures could play important roles in controlling the deadly spread of the disease in the year 2022. During the transmission period, better outcomes might have been achieved in the USA if both controls were brought to action simultaneously. Conclusion: Our study reflects that continuous application of preventive strategies might be an effective tool to prevent the short-term outbreak of mpox or similar diseases. Moreover, such strategies could play supporting roles during pre- and post-vaccination periods.